Bycatch and discards of commercial trawl fisheries in the south coast of Portugal - Costa, Maria Esmeralda de Sá Leite Correia da (2014)
Bycatch and discards are a cause of great concern in commercial world fisheries, with important ecological, economic and conservation implications. With the recent inclusion of a discards ban (‘landing obligation’), in the reform of the EU CFP, these issues have gained a tremendous attention from the economic, scientific, political and social point of view. Demersal trawl fisheries off the southern coast of Portugal capture an extraordinary diversity of species and generate considerable amounts of bycatch and discards. Bycatch includes commercially valuable target-species and bycatch species with low or no commercial value, but the great majority consists of unmarketable species, that are discarded. Bony fishes are dominant in bycatch and discards and the most discarded are of low or no commercial value. The reasons for discarding are fundamentally economic in nature (lack of commercial value) for bycatch species, and legal and administrative (legal minimum landing size) for commercially important species. The study of the reproductive biology of Galeus melastomus, discarded by crustacean trawls, suggests that a minimum landing size should be established for this species, and explains the importance of such a study in the assessment and management of fisheries. The discovery of a new species of the ray Neoraja iberica n. sp. contributes to the knowledge of the local marine biodiversity in Portuguese waters and of the global marine biodiversity. The three cases of abnormal hermaphroditism recorded in Etmopterus spinax, are the first cases known to date of hermaphroditism in this species. There is a need to find solutions to the problem of bycatch and discards of trawl fisheries in the Algarve coast. A combination of technical, regulatory and economic measures to minimize bycatch and reduce discards, before implementing a ‘landing obligation’, is thought to be the best approach to apply in the southern Portuguese multispecies trawl fisheries.